Effect of betel leaf decoction on perineal wound healing in postpartum women - Juspiana; Sulfianti; Nur Eva Sapartina; Mustar (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: Perineal wounds are among the most common complications experienced by postpartum mothers, contributing to discomfort, delayed recovery, and increased risk of puerperal infection. One non-pharmacological treatment widely used in Indonesian traditional medicine is betel leaf (Piper betle) decoction, which contains antibacterial, antiseptic, and anti-inflammatory compounds that may support tissue healing. Despite its extensive use, scientific evidence regarding its effectiveness in perineal wound recovery remains limited, particularly within primary healthcare settings. This study aimed to analyze the effect of betel leaf decoction on perineal wound healing among postpartum mothers in the working area of BLUD UPT Puskesmas Cina. Methods: This quantitative research applied a pre-experimental posttest-only control group design. The study involved 44 postpartum mothers with first- and second-degree perineal wounds selected through purposive sampling. The intervention group received betel leaf decoction treatment twice daily for four days, while the control group received standard postpartum care. Wound healing was assessed using the REEDA scale (Redness, Edema, Ecchymosis, Discharge, Approximation). Data were analyzed using univariate and bivariate techniques to compare healing outcomes between groups. Results: The findings showed that mothers who received betel leaf decoction demonstrated significantly faster wound healing, as reflected by lower REEDA scores compared to the control group. Improvements were observed in reduced redness, edema, and better wound approximation within the first week postpartum. Conclusion: Betel leaf decoction is effective in accelerating perineal wound healing among postpartum mothers. Its traditional use is supported by empirical evidence, indicating potential as a safe, accessible, and affordable complementary therapy in maternal care.